Deregulation of Hippo–TAZ pathway during renal injury confers a fibrotic maladaptive phenotype. Issue 5 (3rd January 2018) - Anorga, Sandybell; Overstreet, Jessica M.; Falke, Lucas L.; Tang, Jiaqi; Goldschmeding, Roel G.; Higgins, Paul J.; Samarakoon, Rohan
Abstract : Although yes‐associated protein (YAP) and transcriptional coactivator with PDZ‐binding motif (TAZ), nuclear transducers of the Hippo pathway, are mostly silent in adult organs, aberrant activation of YAP/TAZ promotes tumorigenesis and abnormal tissue repair. The extent of involvement of TAZ in chronic kidney disease (CKD) is unknown. In our study, increased TAZ nuclear accumulation and expression in the tubulointerstitium was readily evident in 3 models of renal injury including obstructive, aristolochic acid (AA), and diabetic nephropathy, correlating with fibrosis progression. Stable TAZ overexpression in human kidney (HK)‐2 epithelial cells promoted connective tissue growth factor (CTGF), fibronectin, vimentin, and p21 expression, epithelial dedifferentiation, and growth inhibition, in part, via Sma mothers against decapentaplegic homologue (SMAD)‐3‐dependent CTGF induction. CTGF secretion by TAZ‐overexpressing epithelium also triggered proliferative defects in nonengineered HK‐2 cells confirming a nonautonomous role of TAZ (via a paracrine mechanism) in orchestrating kidney epithelial cell‐cell communication. Renal tubular‐specific induction of TGF‐β1 in mice and TGF‐β1 stimulation of HK‐2 cells resulted in TAZ protein up‐regulation. TAZ stable silencing in HK‐2 cells abrogated TGF‐β1–induced expression of target genes without affecting SMAD3 phosphorylation, which is also crucial for fibrotic reprogramming. Thus, TAZ was activated in fibrosis through TGF‐β1–dependent mechanisms and sustained TAZ signaling promotes epithelial maladaptive repair. TAZ is also a novel non‐SMAD downstream effector of renal TGF‐β1 signaling, establishing TAZ as a new antifibrosis target for treatment of CKD.—Anorga, S., Overstreet, J. M., Falke, L. L., Tang, J., Goldschmeding, R. G., Higgins, P. J., Samarakoon, R. Deregulation of Hippo‐TAZ pathway during renal injury confers a fibrotic maladaptive phenotype. FASEB J. 32, 2644–2657 (2018). www.fasebj.org